A measurement application to surfaces using nonlinear interpolation and numerical integration methods - Cano Lengua, Miguel Ángel (2022)
In this article, the area of a two-dimensional surface of the exteriors of the Universidad Nacional Mayor de San Marcos was calculated. It was done using the curve equation integration method, which will be obtained from the perimeter of the sector to be worked on by dividing it into sections, for which Google Maps was used to calculate the reference parameters. In general, not all curve equations are integrable; for this, the approximation methods such as Simpson 3/8, 1/3, and trapezoid were used. In addition, we will apply the Lagrange interpolation to find the equation of the curve; with the results obtained, we make a comparison between the methods, and So we see that the methods differ. Of them, the one with the least margin of error will be taken; these methods can be used in future works where the surface is irregular.